Agricultural intensification in Ghana: Evaluating the optimist’s case for a Green Revolution - Nin-Pratt, Alejandro; McBride, Linden (Elsevier, 2014)
While there are valid reasons for a renewed interest in adapting the lessons of the Asian Green Revolution to the African setting, research must go further in identifying the main, and potentially unique, drivers of agricultural intensification within and across African countries. In this study we look at the case of Ghana to identify whether fast population growth and the remarkable agricultural performance the country has enjoyed in recent years have resulted in favorable conditions for the adoption of Asian-style Green Revolution technologies. Through descriptive analysis combined with empirical assessment of the economic efficiency of agriculture in different production systems and agroecologies we are able assess the relevance of Green Revolution technologies for agricultural production in Ghana. In particular, we analyze whether fertilizer use in Ghana is associated with high population density and intensive cereal production and whether land-intensive innovations are associated with more efficient production practices. Overall, we do not find evidence of Asian-style Green Revolution agricultural intensification in Ghana; in fact, we find no correlation between population density and input intensity. We also find that labor costs still play a major role in Ghanaian agricultural development in limiting the adoption of labor-intensive technologies even in relatively high population density areas.